Waste of rice straw as renewable energy: An overview of the potential availability, content, and production process. Issue 6 (March 2021) - Ana, A; Khoerunnisa, I; Muktiarni, M; Dwiyanti, V; Maosul, A
Abstract: Indonesia's crude oil balance has been in deficit during the last decade. The increase in domestic crude oil consumption is inversely proportional to its production. New crude oil reserves are needed to anticipate a prolonged energy crisis. This study examines the potential of agricultural waste as a renewable energy source that can be produced in terms of availability, content, and production process. A systematic literature review was chosen as the method of this study. The biomass content in agricultural was can be used as bioenergy raw material, one of which is lignocellulose. Rice waste is an agricultural waste that is available in large quantities and contains high lignocellulose. Through biochemical processes, lignocellulose is broken down into lignin in the pre-treatment process. Cellulose is converted into glucose using acids in the process of hydrolysis. The conversion of glucose into ethanol is carried out in the fermentation process. Bioethanol is purified by a distillation process to increase the ethanol content. The high content of lignocellulose in rice waste and high annual production in various regions in Indonesia is a major potential. A comparison of the availability of agricultural waste as raw material for bioethanol is discussed.